A Study on the Pattern of Fingerprint Ridges for Determination of Gender in an Ethnic Tamil Population in Thiruporur Taluk of Tamilnadu - Yamini , R L V; Barman , D D; Ganesh, R (Journal of Indian Academy of Forensic Medicine, 2023)
Human identification is critical, although it might be difficult given that each person has a particular trait. Fingerprint is the best  identification of both living and deceased individual. There are patterns like ridge density, macro characteristic and micro characteristic in  fingerprint. Ridge density and thickness plays major role in differentiation male and female gender. This is comparative study conducted  on 223 volunteers of 125 female and 98 males under the age group varying from 18-65 years in Tamil speaking population in Thiruporur  Taluk. After informed consent and preliminary data, fingerprints were obtained from the volunteers by means of simple inking method as  suggested by Cummins and Midlo for fingerprint pattern we used blue stamp ink with clean and dry hands of all ten fingers, fingerprint  were imprinted on fingerprint format paper. The present study resulted that mean value of ridge density of female vary from 11.2 – 12.7  ridges/mm with average of 11.95 ridges/mm ( ~ 12 ridges/mm ) and mean value of ridge density of male are 12.1 -13.7 ridges/mm with  2 2 2 2 average of 12.9 ridges/mm (~13 ridges/mm ) which shows that male have higher ridge density than female. In our study 'P' valuecompared between male and female showed non-significance in all fingers except little finger which was significant. Fingerprint ridge  density is a very important parameter useful in gender distinction. In this study the fingerprint ridge density was found to be higher in males  than in females. This will be useful among individuals of ethnic Tamil descent to predict the degree of sexual dimorphism based on ridge  density pattern,
Keywords: Fingerprint; Identification; Ridge density; Ethnic; Tamil; Sexual dimorphism